2010
DOI: 10.1016/j.neuroimage.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship of dopamine D2-like receptor availability in striatal and extrastriatal brain regions in healthy humans: A principal component analysis of [18F]fallypride binding

Abstract: Individual differences in dopamine D2-like receptor availability arise across all brain regions expressing D2-like receptors. However, the inter-relationships in receptor availability across brain regions are poorly understood. To address this issue, we examined the relationship between D2-like binding potential (BP ND ) across striatal and extrastriatal regions in a sample of healthy participants. PET imaging was performed with the high affinity D2/D3 ligand [ 18 F]fallypride in 45 participants. BP ND images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 59 publications
12
41
1
Order By: Relevance
“…Previous studies of striatal D2-R have reported no differences (Schneier et al, 2009), or lower levels in patients (Schneier et al, 2000), as compared to the present results of elevated extrastriatal D2-R availability. This apparent discrepancy is however in line with observations of low , or even inverse associations (Zald et al, 2010), between striatal and extrastriatal D2-R levels.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies of striatal D2-R have reported no differences (Schneier et al, 2009), or lower levels in patients (Schneier et al, 2000), as compared to the present results of elevated extrastriatal D2-R availability. This apparent discrepancy is however in line with observations of low , or even inverse associations (Zald et al, 2010), between striatal and extrastriatal D2-R levels.…”
Section: Discussionsupporting
confidence: 80%
“…We hypothesized that differences would be found within brain regions highlighted in activation and blood flow studies of SAD (Freitas-Ferrari et al, 2010;Brühl et al, 2014), and subsequently selected regions of interest (ROIs) for the statistical comparison. Since the HRRT system allows for precise examination of the spatially heterogeneous distribution of D2-Rs observed in the human brain (Zald et al, 2010), a voxel-by-voxel analysis of group differences was also performed, using the combined ROIs as search volume. Since D2-R availability shows low correlations between striatal and extrastriatal regions (Zald et al, 2010;, we investigated differences in D2-R availability in both directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrastriatal VOIs for the hippocampus, amygdala, and thalamus were defined using the FSL software package and a whole striatum VOI was created by combining VOIs of the caudate, putamen, and nucleus accumbens. The functional subdivisions of the striatum (Martinez et al, 2011) and midbrain (Zald et al, 2010) were defined using published guidelines. The cerebellum was selected as an appropriate reference region (Hall et al, 1994;Ishibashi et al, 2013).…”
Section: Mri Scanning and Voismentioning
confidence: 99%
“…It has been revealed to be a therapeutic target for antipsychotic and antiparkinsonian drugs. High degrees of sequence identities are within the trans-membrane helices among D 2 -like receptor [2,13,16,[18][19][20][21], especially between D2R and D3R. Importantly, the near-identity of the residues inferred to form the binding site among them produces a formidable challenge to developing D3R-selective compounds with drug-like physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%